2005
DOI: 10.1007/bf02760574
|View full text |Cite
|
Sign up to set email alerts
|

Early onset neonatal sepsis

Abstract: Screening for sepsis in an asymptomatic neonate is warranted only in the presence of a maternal risk factor even if the neonate is at high risk of developing sepsis due to associated problems of prematurity, low birth weight or asphyxia. Knowledge of likely causative organisms of EOS can aid in instituting prompt and appropriate therapy, in order to minimise morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
100
5
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 10 publications
25
100
5
6
Order By: Relevance
“…Group B streptococcus has been reported uncommonly as a cause of earlyonset sepsis in India. 15,18 The incidence of late onset sepsis secondary to CoNS is less common in developing countries, as also seen in our study. 15,19 The lower rates of infection at our centers could be secondary to less-invasive device use.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Group B streptococcus has been reported uncommonly as a cause of earlyonset sepsis in India. 15,18 The incidence of late onset sepsis secondary to CoNS is less common in developing countries, as also seen in our study. 15,19 The lower rates of infection at our centers could be secondary to less-invasive device use.…”
Section: Discussionsupporting
confidence: 85%
“…15,18 A similar pattern of Gram-negative organisms in neonates with early-onset sepsis is reported by Stoll et al 25 Mortality in neonates with early-onset/perinatal sepsis was more (57%) than in neonates with postnatal/nosocomial sepsis (39%).…”
Section: Discussionsupporting
confidence: 66%
“…The culture positive rate was 54.1% which is comparable to culture positive rate of 43% observed by Chackoo et al, 59.8% by Khatua et al 1,16 This difference in positivity of blood culture is because blood culture positivity depends on many factors like specimen collection, blood volume and the number and timing of blood culture.…”
Section: Discussionsupporting
confidence: 52%
“…Chacko et al, Sharma et al and Choudhary et al reported incidence of septicemia as 37.2/1000 live births, 33.7/1000 and 51/1000 live births respectively. 1,14,15 In present study, as per Table 1, lethargy was most common clinical feature in current study (76.1%) followed by refusal to feed (75.2%), respiratory distress (66.1%), hypothermia (38.5%), hyperthermia (28.4%), abdominal distension (11.9%), jaundice (10.1%), convulsions (10.1%), apnea (7.3%), irritability (3.7%), vomiting (2.8%), sclerema (1.8%) and diarrhea (1.8%). Kathua et al 16 reported refusal to feed as common clinical presentation (92%) followed by lethargy (74%), diarrhea (74%), abdominal distension (60.1%), hypothermia (46.8%), jaundice (38%), vomiting (30.4%), hyperthermia (24.8%), respiratory distress (24%), sclerema (17.4%), apnea (13%) and convulsions (10.8%).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Our results differed from that of Betty Chacko et al who observed an equal proportion of cases among both males and females, because their study involved only early onset septicemia cases. 12 The male preponderance in neonatal septicemia may be linked to the X-linked immuno-regulatory gene factor resulting in the host's susceptibility to infections in males. 13 Maximum culture positive cases were seen in neonates more than 1 week of age 41.6% and Late onset septicemia 87.5% as compared to neonates aged less than 1 week 41.6% and early onset septicemia 12.5% in the present study.…”
Section: Discussionmentioning
confidence: 99%